Reconstruction of chronic radiation-induced ulcers in the chest wall using free and pedicle flaps - Zhou, Bo; Long, Ying; Li, Sha; Lv, Chunliu; Song, Dajiang; Tang, Yuanyuan; Yi, Liang; Luo, Zhenhua; Xiao, Gaoming; Li, Zan; Zhou, Xiao (Frontiers in Surgery, 2022)
Abstract: Background and purpose: Resection of radiation-induced ulcers often causes full-thickness defects of the chest wall. We retrospectively reviewed and evaluated 17 patients to explore a method of chest wall reconstruction. Materials and methods: A total of 17 breast cancer patients with radiation-induced ulcers were included. Various type of prostheses and flaps were used, results of clinic were evaluated. Results: Sixteen patients had full-thickness defects and one patient had only a soft tissue defect and underwent reconstruction with a pedicle latissimus dorsi myocutaneous flap. Among all 16 full-thickness defect cases, 15 patients underwent bony thoracic reconstruction using polymesh /3D-printed titanium plates or methyl methacrylate. For soft tissue reconstruction, 13 patients reconstruction using a free deep inferior epigastric perforator flap in combination with a contralateral transverse rectus abdominis myocutaneous flap, and 2 underwent pure free DIEP flap reconstruction. Among all the patients 15 healed with no complications, and 2 patients had delayed healing on the edges of the flaps. Conclusions: Distant pedicle or free flap can used for soft tissue defect coverage, for those severe patients with full-thickness defects and used prostheses, free deep inferior epigastric perforator flap in combination with a contralateral transverse rectus abdominis myocutaneous flap would be an applicable choice.